Atmospheric VOC measurements at a High Arctic site: characteristics and source apportionment - J. B. Pernov; R. Bossi; T. Lebourgeois; J. K. Nøjgaard; R. Holzinger; J. L. Hjorth; H. Skov (Atmospheric Chemistry and Physics, 2021)
There are few long-term datasets of volatile organic compounds (VOCs) in the High Arctic. Furthermore, knowledge about their source regions remains lacking. To address this matter, we report a multiseason dataset of highly time-resolved VOC measurements in the High Arctic from April to October 2018. We have utilized a combination of measurement and modeling techniques to characterize the mixing ratios, temporal patterns, and sources of VOCs at the Villum Research Station at Station Nord in northeastern Greenland. Atmospheric VOCs were measured using proton-transfer-reaction time-of-flight mass spectrometry. Ten ions were selected for source apportionment with the positive matrix factorization (PMF) receptor model. A four-factor solution to the PMF model was deemed optimal. The factors identified were biomass burning, marine cryosphere, background, and Arctic haze. The biomass burning factor described the variation of acetonitrile and benzene and peaked during August and September. The marine cryosphere factor was comprised of carboxylic acids (formic, acetic, and C 3 H 6 O 2 ) as well as dimethyl sulfide (DMS). This factor displayed peak contributions during periods of snow and sea ice melt. A potential source contribution function (PSCF) showed that the source regions for this factor were the coasts around southeastern and northeastern Greenland. The background factor was temporally ubiquitous, with a slight decrease in the summer. This factor was not driven by any individual chemical species. The Arctic haze factor was dominated by benzene with contributions from oxygenated VOCs. This factor exhibited a maximum in the spring and minima during the summer and autumn. This temporal pattern and species profile are indicative of anthropogenic sources in the midlatitudes. This study provides seasonal characteristics and sources of VOCs and can help elucidate the processes affecting the atmospheric chemistry and biogeochemical feedback mechanisms in the High Arctic.